Factors influencing the outcome of non-surgical periodontal treatment: a multilevel approach - Cristiano Tomasi (Blackwell Synergy, 2007)
Aim: To investigate, by means of multilevel analysis, factors that may affect the short-term clinical outcome of non-surgical periodontal treatment. Materials and Methods: Forty-one patients randomly assigned to two protocols of non-surgical therapy were included. The impact of different covariates on the probability of ‘‘pocket closure’’ [i.e. probing pocket depth (PPD)44 mm] was explored using a logistic multilevel model. The impact on the final PPD was explored using a continuous multilevel model. Results: The logistic model revealed a significant impact of smoking (po0.001), presence of plaque at the site (po0.001) and location of the pocket at a multi-rooted tooth (po0.001). The model explained 44% of the total variability. Of the unexplained variance, 19% was attributed to inter-patient variability. The continuous model revealed the same factors to be significant and an additional significant impact of interactions between the covariates. The R2 was 0.50 and the random slopes model revealed an increase in the variability of the final pocket depth with an increase in the initial PPD. Conclusion: Smoking habits, plaque at site level and tooth type were significant factors in determining the short-term clinical outcome of non-surgical periodontal treatment.